The genus Potamobates Champion in Ecuador, with description of P. shuar n. sp. (Hemiptera: Gerridae) - Buzzetti, Filippo M. (Zootaxa, 2006)
Potamobates horvathi Esaki and P. anchicaya Polhemus & Polhemus are reported for Ecuador for the first time. P. shuar n. sp. is described from southern Ecuadorean Amazonas. Male and female genitalia separate P. shuar from other congeneric species. Five species of Potamobates occurr in Ecuador: P. anchicaya, P. horvathi, P. shuar n. sp., P. sumaco Cognato, and P. williamsi Hungerford. Finally, comments on the phylogeny of the genus are given.